Nomenclatural notes for Megachiline bees (Hymenoptera: Megachilidae) - Engel, Michael S. (Academia Journal of Biology, 2024)
Recent changes to the generic classification of Megachilini necessitate several nomenclatural changes for species of the tribe. Four specific epithets were considered junior homonyms in a retrograde classification of Megachile Latreille and were therefore renamed. These epithets are resurrected as they are no longer congeneric with their senior homonyms (ICZN: Art. 59.4), and their former replacements are now considered junior synonyms: Callomegachile (Callomegachile) elegans (Cheesman) (= Chalicodoma (Callomegachile) cheesmanae Michener, new synonymy), Callomegachile (Callomegachile) gigas (Wu) (= Megachile (Callomegachile) parornata Chatthanabun, Warrit, and Ascher, new synonymy), Chelostomoides (Chelostomoides) pedalis Raw (= Megachile (Chelostomoides) rawi Engel, new synonymy), Megachile (Creightonella) aurantiaca Rebmann (= Megachile (Creightonella) taftanica Engel, new synonymy). In addition, four replacement names (nomina nova) are established: Megachile (Chelostomoda) zyzzyx Engel (for Megachile (Chelostomoda) indica (Gupta)), M. (Eurymella) bakololo Engel (for Megachile (Eurymella) zambesica Pasteels), Coelioxys silaneg Engel (for Coelioxys genalis Pasteels), and Coelioxys qi Engel (for Coelioxys brevicaudatus Friese).